Health-related quality of life in children after surgical repair of esophageal atresia: a cross-sectional study in China - Feng, Zhong; Zhu, Haitao; He, Weijing; Peng, Xueni; Gao, Runnan; Tian, Yuxin; Cao, Xuqing; Chen, Gong; Dong, Kuiran; Zheng, Shan; Shen, Chun (Frontiers in Pediatrics, 2024)
Objective To investigate health-related quality of life (HRQOL) in patients after surgical repair for esophageal atresia (EA) and identify its potential influencing factors. Methods A total of 102 EA children who had previously visited our hospital participated in this cross-sectional study. Basic data and disease data of the patients were collected. The HRQOL was measured with the Pediatric Quality of Life Inventory™4.0 (PedsQL™4.0) and EA-QOL questionnaire and ranked on a reverse 0–100 scale, with a higher number indicative of a better HRQOL perception. The scores of PedsQL™4.0 in children with EA were collected and compared with that of the demographically matched healthy control group. Meanwhile, the condition-specific HRQOL of EA was analyzed by the EA-QOL questionnaire, and the potential clinical factors that influenced the HRQOL were determined by the generalized linear model. Results The group of EA and control reached a similar score in the generic PedsQL™4.0 (EA group: 86.55 ± 9.69; control group: 89.41 ± 6.54; p = 0.670). There was no significant difference between the EA group and the control group in other domains except the school functioning. Condition-specific HRQOL in the 2–7-year-old group had the highest score in social isolation and stress domain and the lowest score in the physical health and treatment domain, with an overall quality of life score of 83.48 ± 10.22. The scores of the 8–17-year-old group were relatively high in social relationships and health and well-being and lowest in the eating domain, with an overall quality of life score of 89.43 ± 8.57. Heart malformation, complicated esophageal surgery history, respiratory symptoms,and digestive symptoms in the past 1 month were the main factors affecting the HRQOL of children aged 2–7 years. Complicated esophageal surgery history, respiratory symptoms, and digestive symptoms in the past 1 month were the main factors affecting the HRQOL of children aged 8–17 years. Conclusions The findings suggest that patients with EA generally had a good HRQOL. However, EA children with postoperative complications and associated symptoms have lower scores in the EA-QOL questionnaire.